A screening approach to improve water management practices in undeveloped shale plays, with application to the transboundary Eagle Ford Formation in northeast Mexico. (15th April 2019) - Hernández-Espriú, Antonio; Wolaver, Brad; Arciniega-Esparza, Saúl; Scanlon, Bridget R.; Young, Michael H.; Nicot, Jean-Philippe; Macías-Medrano, Sergio; Breña-Naranjo, J. Agustín
Abstract: Hydraulic fracturing (HF) operations have transformed the unconventional energy industry, leading to a global increase in hydrocarbon production. Despite this, only the US, China, Canada and Argentina currently dominate production of unconventional resources, with the majority of shale basins globally remaining unprofitable to develop. An important gap in current water-energy nexus research, which this study addresses, is the assessment of potential water use to satisfy HF procedures in emergent plays. This work presents a screening tool for assessing first-order estimates of water impacts in undeveloped shale plays, testing the approach in the transboundary Eagle Ford (EF) play in northeast Mexico. We couple surface water and groundwater stress indicators derived from global hydrological variables to depict a baseline water stress index. Relative water stress is mapped for proposed blocks to be leased by the Mexican government in the future. We simulate four HF scenarios to assess new total water stress indicators for each block, considering shale production schemes using representative well drilling density (well lateral length(s) per unit area) and HF water intensity (HF water volume per unit lateral length) from existing EF development in Texas. Results suggest that the most feasible management scenario would consider the drilling of ∼1360 new unconventional wells/yr with projected HF water use of ∼57 Mm 3 /yr (0.7% of the total water withdrawals). The remaining scenarios will largely affect groundwater resources. Though applied to the EF in Mexico, this screening tool can assess water use constraints in emerging unconventional plays globally. Highlights: A screening approach for assessing water impacts in shale plays is presented. Water indicators were coupled to depict a baseline index in northeast Mexico. We simulate hydrofracturing scenarios using water use from development in Texas. Some management schemes prove that shale production will affect local groundwater. This method can be used to evaluate water constraints in semiarid plays globally.